Functions of Teachers’ Paralanguage in Online Classroom Interaction (Zoom Cloud Meetings) - Murni Mahmud; Maemuna Muhayyang; Anindya Anisa Ayuningsih (Interference: Journal of Language, Literature, and Linguistics, 2023)
Abstract. This paper aims to investigate the use of paralanguage, as a part of non-verbal communication. It is believed that paralanguage has fruitful contribution to the successful teaching and learning process and therefore it is necessary to explore deeply about the functions of teachers’ paralanguage in the classroom interaction. Under the design of qualitative research, this study focused on observing the functions of teachers’ paralanguage in online classes conducted via Zoom Cloud Meetings. This study relied on the use of observation and recording to obtain data. The subject is one English class with one teacher and 31 students in one Senior High School in South Sulawesi, Indonesia, which applied Zoom Cloud Meetings as the medium of interaction. To analyze data, steps of analysis included data collection, data reduction, data display and conclusion (drawing or verifying) . The result of data analysis showed that the use of teacher’s paralanguage in teaching has several functions. Some of those functions were (1) to accent, (2) to complement, (3) to contradict, (4) to regulate, and (5) to repeat. Findings from this study can become a reference for teachers in creating effective classroom interaction both in face-to-face interaction and online interaction. The results of this study are expected to give a contribution to pedagogical knowledge as an important input about non-verbal communication, especially the use of paralanguage in EFL classroom interaction.  Keywords: Communication; Non-Verbal Communication; Paralanguage; EFL Classroom Interaction; Online Classes